SOX4 and SMARCA4 cooperatively regulate PI3k signaling through transcriptional activation of TGFBR2 - Gaurav A. Mehta (Nature Portfolio, 2021)
Abstract Dysregulation of PI3K/Akt signaling is a dominant feature in basal-like or triple-negative breast cancers (TNBC). However, the mechanisms regulating this pathway are largely unknown in this subset of aggressive tumors. Here we demonstrate that the transcription factor SOX4 is a key regulator of PI3K signaling in TNBC. Genomic and proteomic analyses coupled with mechanistic studies identified TGFBR2 as a direct transcriptional target of SOX4 and demonstrated that TGFBR2 is required to mediate SOX4-dependent PI3K signaling. We further report that SOX4 and the SWI/SNF ATPase SMARCA4, which are uniformly overexpressed in basal-like tumors, form a previously unreported complex that is required to maintain an open chromatin conformation at the TGFBR2 regulatory regions in order to mediate TGFBR2 expression and PI3K signaling. Collectively, our findings delineate the mechanism by which SOX4 and SMARCA4 cooperatively regulate PI3K/Akt signaling and suggest that this complex may play an essential role in TNBC genesis and/or progression.